The Complex α-μ Fading Channel with OFDM Application - Wander H. M. Freitas; Roberto C. D. V. Bomfin; Rausley A. A. de Souza; Michel Daoud Yacoub (International Journal of Antennas and Propagation)
The aims of this paper are threefold: (i) to present a model for the complex α-μ fading channel; (ii) to propose an efficient, simple, and general method to generate complex α-μ samples; (iii) to make use of this channel in order to assess the bit error rate performance of an OFDM system. An analytical framework is then used, whose output is validated through Monte Carlo simulation. Several important conclusions concerning the system performance as a function of the channel parameters, namely, nonlinearity, clustering, and power imbalance of in-phase and quadrature components, are drawn.